Teachers trust educational science - Especially if it confirms their beliefs - Schmidt, Kirstin; Rosman, Tom; Cramer, Colin; Besa, Kris-Stephen; Merk, Samuel (Frontiers in Education, 2022)
Teachers around the world are increasingly required by policy guidelines to inform their teaching practices with scientific evidence. However, due to the division of cognitive labor, teachers often cannot evaluate the veracity of such evidence first-hand, since they lack specific methodological skills, such as the ability to evaluate the design of the study. For this reason, second-hand evaluations come into play, during which individuals assess the credibility and trustworthiness of the person or other entity who conveys the evidence instead of evaluating the information itself. In doing so, teachers' belief systems (e.g., beliefs about the trustworthiness of different sources, about science in general or about specific educational topics) can play a pivotal role. But judging evidence based on beliefs may also lead to distortions which, in turn, can result in barriers for evidence-informed school practice. One popular example is the so-called confirmation bias, that is, preferring belief-consistent and avoiding or questioning belief-inconsistent information. Therefore, we experimentally investigated (1) whether teachers trust knowledge claims made by other teachers and scientific studies differently, (2) whether there is an interplay between teachers' trust in these specific knowledge claims, their trust in educational science, and their global trust in science, and (3) whether their prior topic-specific beliefs influence trust ratings in the sense of a confirmation bias. In an incomplete rotated design with three preregistered hypotheses, N=414 randomly and representative sampled in-service teachers from Germany indicated greater trust in scientific evidence (information provided by a scientific journal) compared to anecdotal evidence (information provided by another teacher on a teacher blog). In addition, we found a positive relationship between trust in educational science and trust in specific knowledge claims from educational science. Finally, participants also showed a substantial confirmation bias, as they trusted educational science claims more when these matched (rather than contradicted) their prior beliefs. Based on these results, the interplay of trust, educational research literacy and evidence-informed school practice is discussed.